2020
DOI: 10.1109/access.2020.2974158
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Detection of Non-Proliferative Diabetic Retinopathy in Optical Coherence Tomography Images Using Convolutional Neural Networks

Abstract: Diabetic retinopathy (DR) is a disease that forms as a complication of diabetes. It is particularly dangerous since it often goes unnoticed and can lead to blindness if not detected early. Despite the clear importance and urgency of such an illness, there is no precise system for the early detection of DR so far. Fortunately, such system could be achieved using deep learning including convolutional neural networks (CNNs), which gained momentum in the field of medical imaging due to its capability of being effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 62 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…It is done by trained experts where the images are used to diagnose the fatal diseases, and it is named deep CNN models. Ghazal et al (2019) observed a non-proliferative diabetic retinopathy using CNN. The author addresses the computeraided diagnostic (CAD) system to detect non-proliferative DR (NPDR) usingCNN.…”
Section: Introductionmentioning
confidence: 99%
“…It is done by trained experts where the images are used to diagnose the fatal diseases, and it is named deep CNN models. Ghazal et al (2019) observed a non-proliferative diabetic retinopathy using CNN. The author addresses the computeraided diagnostic (CAD) system to detect non-proliferative DR (NPDR) usingCNN.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical hazards of PDR mainly to lead to blindness and increase the risk of poor prognosis [ 1 ]. At present, vitrectomy combined with panretinal laser photocoagulation is commonly used in practice, but patients are prone to bleeding and iatrogenic retinal breaks during surgery, and postsurgical complications such as vitreous rehemorrhage and retinal detachment seriously affect the surgical effect, which may result in patients' irreversible loss of vision [ 2 ]. According to its pathological characteristics, perioperative application of anti-VEGF drugs or anti-inflammatory drugs can reduce intraoperative blood loss and the probability of postsurgical complications.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [ 183 ] applied a deep network, called OCTD_Net, for early detection of DR using OCT images. Ghazal et al [ 184 ] developed early detection of NPDR using OCT images based on an AlexNet followed by an SVM for classification.…”
Section: The Role Of Ai In the Early Detection Diagnosis And Grading ...mentioning
confidence: 99%